ANCA-associated vasculitis and the impact of diffuse alveolar hemorrhage in elderly patients: a retrospective cohort study - Schaier, Matthias; Kälble, Florian; Benning, Louise; Reichel, Paula; Mahler, Christoph; Nußhag, Christian; Rusnak, Jonas; Gutting, Tobias; Preusch, Michael; Zeier, Martin; Morath, Christian; Speer, Claudius (Rheumatology international, 2025)
The ANCA-associated vasculitis (AAV) has an exceptionally high morbidity and mortality especially in patients with diffuse alveolar hemorrhage (DAH). Data on DAH in elderly AAV patients is still very limited. To investigate the impact of DAH on patient survival, relapse-free survival, death from infectious complications, and the incidence of pneumonia in one of the most vulnerable but often underrepresented AAV subpopulation—elderly patients. We included 139 AAV patients in this retrospective cohort study and performed a 5-year follow-up. AAV patients were divided into patients ≤ 65 and > 65 years (“elderly”). Elderly AAV patients were further subdivided into patients with and without DAH. Relapse-free survival was comparable (P = 0.49) whereas overall patient survival (P = 0.01) was significantly lower in patients > 65 as compared to ≤ 65 years. Death due to infectious complications occurred more frequently in the elderly cohort (log-rank P = 0.02). Especially the incidence of pneumonia (including opportunistic pathogens) was considerably higher in elderly AAV patients (log-rank P = 0.001). Overall survival in elderly patients was significantly lower in patients with as compared to patients without DAH [8/18 (44%) versus 9/52 (17%) deaths (P = 0.02)] while relapse-free survival was again comparable (P = 0.87) between both groups. Notably, 6 out of 8 fatal outcomes in elderly DAH patients were associated with severe infections. In multivariate analyses, age and glucocorticoid (GC) dose at 3 months were the only predictors of death from infectious complications, whereas this could not be independently demonstrated for DAH. Life-threatening infections with (opportunistic) pneumonia are common in elderly AAV patients with DAH during the first 12 months and higher GC dose was an independent predictor of death from infectious complications.